In vivo immunotoxicity evaluation of Gd2O3 nanoprobes prepared by laser ablation in liquid for MRI preclinical applications - Tian, Xiumei; Guan, Xiaoying; Luo, Ningqi; Yang, Fanwen; Chen, Dihu; Peng, Ye; Zhu, Jixiang; He, Fupo; Li, Li; Chen, Xiaoming (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2014)
Gd 2 O 3 nanoprobes prepared by laser ablation in liquid can be used as magnetic resonance imaging contrast agent. However, their immunotoxicity in vivo remains unknown. In this article, the in vitro biocompatibility of the Gd 2 O 3 nanoprobe was evaluated in terms of cell uptake, cell viability, and apoptosis. In vivo immunotoxicity was detected by monitoring the levels of the immunity mediator, cluster of differentiation (CD) markers in Balb/c mice. The results show that no in vitro cytotoxicity was observed, and no significant changes in the expression levels of CD206 and CD69 between the nanoprobe-injected group and the Gd-DTPA group in mice were observed. Importantly, the immunotoxicity data revealed significant differences in the expression levels of CD40, CD80, CD11b, and reactive oxygen species. In addition, transmission electron microscopy images showed that few Gd 2 O 3 nanoprobes were localized in phagosomes by the endocytic pathway. In conclusion, the toxic effects of our Gd 2 O 3 nanoprobe may be due to endocytosis during which the microstructure or ultrastructure of cells is slightly damaged and induces the generation of an oxidative stress reaction that further stimulates the innate immune response. Therefore, it is important to use a sensitive assay for the in vivo immunotoxicity measurements to evaluate the risk assessment of Gd 2 O 3 -based biomaterials at the molecular level.